The influence of living a calling on work continuity intentions and the mediating effects of subjective age and occupational future time perspective - Anderson, Kemol, author; Cleveland, Jeanette N., advisor; Kraiger, Kurt, committee member; Dik, Bryan J., committee member; Shore, Lynn M., committee member (Colorado State University. Libraries, 2019)
Employee withdrawal has historically been – and continues to be – of significant concern to organizations. The present study investigates the effects of living a calling on work continuity intentions, specifically: turnover intentions, planned retirement age, intentions to retire fully, intentions to pursue career-related bridge employment, and intentions to pursue non-career related bridge employment. Drawing from continuity theory and socioemotional selectivity theory, it was hypothesized that the relationship between living a calling and these later career stage outcomes would be mediated by subjective age and occupational future time perspective (OFTP). The hypothesized mediated model was tested at two time points, one month apart. Using a sample of 266 at Time 1 and 171 at Time 2, Mturk participants completed surveys about their personal characteristics, job attitudes, and intentions regarding turnover and retirement. Results using the predictor and mediators at Time 1 and outcome variables at Time 2 showed that OFTP, but not subjective age, mediates the relationship between living a calling and turnover intentions, intentions on fully retiring and intentions to pursue non-career related bridge employment. Findings of the cross-sectional model suggest that OFTP, but not subjective age, mediates the relationship between living a calling and turnover intentions, as well as intentions to pursue career-related bridge employment and non-career related bridge employment. Theoretical and practical implications are discussed, and suggestions for future research are presented.
Keywords: calling; OFTP; subjective age; occupational future time perspective; bridge employment; retirement